2005
DOI: 10.1007/s00213-005-0167-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the novel kappa opioid receptor antagonist, JDTic, on reinstatement of cocaine-seeking induced by footshock stressors vs cocaine primes and its antidepressant-like effects in rats

Abstract: Depression and stress are two states during cocaine abstinence which users identify as precipitating relapse, and JDTic may have properties which attenuate both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
388
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(412 citation statements)
references
References 37 publications
22
388
2
Order By: Relevance
“…The findings of the present study are consistent with previous reports (Beardsley et al 2005;Carey et al 2007;Valdez et al 2007). Beardsley et al (2005) showed that intermittent and uncontrollable footshock was able to reinstate active lever responding on a lever previously associated with cocaine self-administration and that pre-treatment with the kappa antagonist JDTic attenuated footshock-induced cocaine-seeking behavior.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The findings of the present study are consistent with previous reports (Beardsley et al 2005;Carey et al 2007;Valdez et al 2007). Beardsley et al (2005) showed that intermittent and uncontrollable footshock was able to reinstate active lever responding on a lever previously associated with cocaine self-administration and that pre-treatment with the kappa antagonist JDTic attenuated footshock-induced cocaine-seeking behavior.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with this prediction, rodents given either an intermittent footshock or a forced swim stressor failed to reinstate drug-seeking behaviors after administration of kappa receptor antagonists (Beardsley et al 2005;Carey et al 2007). In this study, we extend these findings by determining the effects of the kappa antagonist norbinaltorphimine and disruption of the kappa system by gene deletion of either the kappa opioid receptor or the endogenous ligand dynorphin on forced-swim-stress-and foot-shockstress-induced reinstatement of cocaine-conditioned place preference.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Finally, JDTic ((3R)-7-hydroxy-N-((1S)-1-([(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl)-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide) is a potent and selective kappa-opioid receptor antagonist [90] that has been reported to have antidepressantlike effects [91]. Such antidepressant activity could be mediated by blockade of monoamine transporters.…”
Section: Miscellaneous Drugsmentioning
confidence: 99%